Human implantation: The complex interplay between endometrial receptivity, inflammation, and the microbiome. (January 2022) - Sehring, Jacqueline; Beltsos, Angeline; Jeelani, Roohi
Abstract: Human embryo implantation is an intricate spatiotemporal process that involves the intimate association between the embryo and the endometrium of the mother. During implantation, the endometrium undergoes a dynamic cascade of gene activation and repression, largely driven by autocrine, paracrine, and endocrine action. Steroid hormones, such as estrogen and progesterone, act on a variety of targets including cellular adhesion molecules (CAMs), cytokines, and growth factors to facilitate the implantation process. Given the synchrony required to achieve implantation, it is unsurprising that embryo implantation represents a substantial problem for infertility patients. This is due to a complex interplay taking place at the level of the endometrium. This review discusses the intricacies of embryo implantation including the window of implantation, the cyclical phases of the endometrium, the implantation process itself, and features of endometrial receptivity. Additionally, we will discuss new research regarding inflammatory reproductive biology, epigenetics and microRNA, and the role of the vaginal and endometrial microbiome in implantation. A better understanding of embryo implantation and the interactions occurring at the level of the blastocyst and the endometrium will improve patient care for infertile patients who experience this frustrating challenge. Highlights: While there have been great advances in ART techniques leading to improved fertilization rates, pregnancy rates have remained fairly unchanged suggesting our understanding of endometrial receptivity and implantation is lacking. The expression of integrins (specifically ɑvβ3 integrin), CD44, hyaluronic acid, osteopontin, and HOX genes vary throughout the endometrial phase and likely contribute to successful implantation. Emerging evidence suggests that epigenetic modifications, such as DNA methylation, histone modification, and microRNAs, modulate the expression of the above genes in order to facilitate implantation. Implantation and early pregnancy is characterized as a pro-inflammatory state and is facilitated by natural killer cells and several cytokines. The vaginal and endometrial microbiome impact the environment for the embryo and contribute to implantation success.